MENINGKATKAN DAYA SAING MELALUI PENGEMBANGAN KEWIRAUSAHAAN - Pasrizal, Himyar (JURIS (Jurnal Ilmiah Syariah), 2011)
One’s successes in deed are more dominantly determined by his ability to manage himself and others (soft skill). Soft skills including entrepreneurship encourage people to gain great success and even take over world’s economy and business. In addition, soft skill can reduce ‘sanglaritis’ a mental condition of a labor who keeps seeking for the opportunity to become civil servant or company’s officer which in turn makes them unable and has no desires to create their own business. It is entrepreneurship development which is believed to be able to promote sense of competition among those people through formal and informal trainings.